2010
DOI: 10.1088/0963-0252/19/3/034022
|View full text |Cite
|
Sign up to set email alerts
|

A review of electrodynamic tethers for science applications

Abstract: Abstract. A bare electrodynamic tether (EDT) is a conductive thin wire or tape tens of kilometres long, which is kept taut in space by gravity gradient or spinning, and is left bare of insulation to collect (and carry) current as a cylindrical Langmuir probe in an ambient magnetized plasma. An EDT is a probe in mesothermal flow at highly positive (or negative) bias, with a large or extremely large 2D sheath, which may show effects from the magnetic self-field of its current and have electrons adiabatically tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Ambient sulphur/oxygen ions impacting the tape both leave as neutrals and liberate additional secondary electrons, which are accelerated along magnetic field lines and could excite neutral molecules in the upper Jovian atmosphere, generating auroral emissions. Additionally, switching the contactor off would produce a large surge in both current and radiated power, setting up bias/current pulses along its length which are capable of emitting signals under a transmission line modeling [ Sanmartin , 2010]. It was recently suggested that current modulation in tethers might generate nonlinear, low frequency wave structures attached to the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient sulphur/oxygen ions impacting the tape both leave as neutrals and liberate additional secondary electrons, which are accelerated along magnetic field lines and could excite neutral molecules in the upper Jovian atmosphere, generating auroral emissions. Additionally, switching the contactor off would produce a large surge in both current and radiated power, setting up bias/current pulses along its length which are capable of emitting signals under a transmission line modeling [ Sanmartin , 2010]. It was recently suggested that current modulation in tethers might generate nonlinear, low frequency wave structures attached to the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…Following Vahala and Montgomery (1971), the dependent variables are written as made of three contributions of disparate magnitude, in a double independent linearization…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The general formalism for a uniform pumped wave was first introduced by Nishikawa (1968). The parametric instability, has been predicted by Vahala and Montgomery (1971), before being observed in the laboratory (Lehane and Paoloni, 1972). The theoretical model was extended to include Hall and resistivity terms (Cramer, 1975) and boundary effects (Cramer and Sy, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, spacecraft charging is a serious and practical concern in space engineering, and there have been extensive research activities aimed to address these issues. Among all approaches, tethering systems are quite effective to investigate the charging [3] and magnetic field effects [4], and there are some recent review papers in the literature [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%